Proteksi Atas Barang Milik Daerah Dalam Mewujudkan Akuntabilitas di BPKAD Provinsi Sumatera Utara - Nasution, Dito Aditia Darma; Erlina, Erlina (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
This research aims to analyze and describe the implementation of Regional Property protection in realizing accountability in BPKAD of North Sumatera Province. The method uses in this research is qualitative approach by interviews with employees in the field of accounting and assets. The result shows that the Regional Property protection in BPKAD of North Sumatera Province was effective but was not accountable yet. The newness that made this research different from previous research was researcher added Native Revenue (PAD) to assessed accountability in protect possession of the region. Keywords : Regional Property Protection; Regional Original Income; Accountability.